2000
DOI: 10.3168/jds.s0022-0302(00)75120-4
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of Amino Acids Flowing to the Abomasum into Feed, Bacterial, Protozoal, and Endogenous Fractions

Abstract: We partitioned the flow of amino acids (AA) to the abomasum among rumen undegradable protein (RUP) and bacterial, protozoal, and endogenous fractions using four Holstein cows in midlactation that were equipped with ruminal and abomasal cannulas. A 2 x 2 factorial design with four diets, combinations of high or low ruminally degradable organic matter, and rumen degradable protein, was employed. Crude protein (CP) and AA contents of ruminal bacteria and protozoa and abomasal digesta were determined. Equations fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 20 publications
2
34
0
1
Order By: Relevance
“…Van Bruchem et al (1997) used a continuously abomasal infusion of 15 N-labelled, grass meal-beer yeast suspension and reported that the endogenous contribution accounted for 12% of the duodenal N flow in sheep. N from the endogenous origin varied between <1% (Shabi et al, 2000) and 32% (Larsen et al, 2001) of the duodenal flow of total N in dairy cows using a mathematical approach to estimate the composition of AA from each origin. Sandek et al (2001) reported that endogenous N contributed to 3% up to 12% of the duodenal flow of total N determined by 15 N-labelled method in sheep fed for diets ranging from 15% to 25% crude fibre content.…”
Section: Estimation Of Endogenous N and Aa Flowsmentioning
confidence: 99%
“…Van Bruchem et al (1997) used a continuously abomasal infusion of 15 N-labelled, grass meal-beer yeast suspension and reported that the endogenous contribution accounted for 12% of the duodenal N flow in sheep. N from the endogenous origin varied between <1% (Shabi et al, 2000) and 32% (Larsen et al, 2001) of the duodenal flow of total N in dairy cows using a mathematical approach to estimate the composition of AA from each origin. Sandek et al (2001) reported that endogenous N contributed to 3% up to 12% of the duodenal flow of total N determined by 15 N-labelled method in sheep fed for diets ranging from 15% to 25% crude fibre content.…”
Section: Estimation Of Endogenous N and Aa Flowsmentioning
confidence: 99%
“…Furthermore, in a second study in lactating cows using an infusion of 15 N-leucine (Ouellet et al, 2005), the endogenous contribution to duodenal N flow averaged 18% when silage was fed, and 20% when hay was offered, representing in this latter case, 5.9 g of N/kg of DMI. In dairy cows, using a mathematical approach including estimates of the composition of AA in each fraction, N from endogenous origin varied between <1% (Shabi et al, 2000) and 32% (Larsen et al, 2001) of total duodenal N flow.…”
Section: Duodenal Flowmentioning
confidence: 99%
“…Recently, linear programming was used to partition N flowing to the duodenum into feed, bacteria, protozoa, and endogenous fractions (Shabi et al, 2000;Reynal et al, 2003). Using the same approach, we have calculated the relative proportions of SAB and LAB in duodenal content (Vlaeminck et al, 2006).…”
Section: Introductionmentioning
confidence: 99%